Rural community participation in sustainable management of the Niger delta forests, Nigeria - Ezenwaka, Jasper (Cranfield University, 2018)
The Niger Delta region has been well-known for its crude oil, which provides over 80% of Nigeria’s annual income and since the 1990s, it has been known for armed conflicts and hostilities. The region is generally under-developed and the environment is being degraded as people try to secure their livelihoods. This thesis aims to identify the ecosystem benefits derived from the Niger Delta environment by local communities; appraise the methods of forest management and their effectiveness to provide a steady flow of the ecosystem benefits; identify stakeholders in the use and management of forest ecosystems, and suggest methods of collaborative forest resources management. The research adopted deductive and inductive social research methods to obtain primary data and was guided by three frameworks: livelihoods, ecosystems services, and the stakeholder participation and analysis. The result showed that the rural dwellers of the Niger Delta depend almost entirely on ecosystem benefits for their survival; they have no access to crude oil but can access forest goods and services. The urban dwellers were aware of the range of provisioning, regulatory, cultural, and supporting services but rural dwellers were mainly only aware of provisioning services. The forest stakeholders were identified to comprise rural dwellers, local NGOs, academic and research institutions (classified as subjects); international agencies such as the UN (classified as key players); wood-based industries and urban dwellers (classified as crowd); and the government and oil exploration companies (classified as context setters). The existing forest management approaches included effective community traditional approaches (where they exist) and government laws and policies establishing forest reserves, which were mainly found to be ineffective. At present, the main forest management approach is top-down and initiated by government. The full cohorts of stakeholders are not working together to ensure the effective management of these resources. This thesis recommends a collaborative forest management approach, which involves identified key stakeholders.
Keywords: Ecosystem services; lifelihoods; stakeholder participation; policy; forest conservation